(untitled) (The Journal of Psychology and Sociology, 2017)
Social Partnership serves an important form of regulation of the relations of the interacting parties in terms of the labor market. As the complexity of social life and the growth of the need to resolve the interests of many social groups, it is necessary to use the technology of social partnership as a mechanism for cooperation and solidarity among the cooperating parties. The origins of social partnership is associated with the emergence of the trade union movement at work, which made the spontaneous interaction in the form of socio-economic protests to civilized settlement of the interests of the parties to labor relations.Passionary nature of modern social technologies evident in their focus on the effective solution of problems with the joint efforts of the parties. The formation of such qualities of the modern professional market society as competitiveness, professionalism and initiative is only possible through the use of modern social technologies that take into account the basic rules of social management.University main supplier of qualified personnel must function effectively in order to compete in a globalized international and domestic level and take its rightful place in the ranking system. This requires to meet all the requirements on the part of employers in the face of the state, businesses and public organizations. Employers, in turn, are interested in getting quality training, and to create conditions for imparting practical skills of students and graduates. This forces them to their own interests and requirements of public authorities, on the basis of binding official documents regulate partnerships.